HUMANIZATION IN THE MANAGEMENT OF THE NURSING TEAM - Cardoso, Manuela; Silva, Mariana; Pereira, Sandra (Health and Society, 2023)
Of the problems that nurses face today, such as lack of human resources, lack of material resources, poor working conditions, overload of schedules, lack of professional appreciation, what causes them the most dissatisfaction is the lack of humanization by their hierarchical superiors and bosses. Nurses need to be considered, respected and valued in their workplace. The training of managers aims to develop leadership that inspires its employees by investing in proximity and individual and professional development. Knowledge/training in the area of human relations may be the key to assertiveness for future nurse managers, which will be reflected in the feeling of protection of those who provide care. It is important to make a serious investment in Leaders and Managers who are aware of the humanized care of their teams.